A Review of Extraction Methods for Obtaining Bioactive Compounds in Plant-Based Raw Materials - VEREP, Didem; ATEŞ, Saim; KARAOĞUL, Eyyüp (Bartin Orman Fakultesi Dergisi, 2023)
In recent years, the usage of lignocellulosic biomasses in food supplements has become popular. The studies about the development of reliable and short-term methods in the extraction of these active components in lignocellulosic biomasses and the usage of eco-friendly solvents have increased gradually. Traditional extraction methods take a long time and use a large amounts of organic solvents. In addition, the damages of used organic solvents to the environment are high considerably. For this reason, the need for technologies that reduce the extraction time and reduce the use of organic solvents and environmentally friendly "green chemistry" solvents is increasing day by day. In this review, traditional and modern extraction methods were examined and general application areas of these methods were introduced. Traditional extraction methods include maceration, pressing, infusion, digestion, percolation, decoction, reflux, tincture, distillation, and soxhlet methods, and modern extraction methods including pressurized liquid extraction, supercritical fluid extraction, ultrasonic assisted extraction, microwave assisted extraction, pulsed electric field extraction, enzyme assisted extraction methods, and their variation parameters were investigated. It has been seen that modern extraction methods are performed in less amount of sample, lower volume of solvent, lower energy consumption, and shorter extraction times compared to traditional methods. Within the scope of the study, considering all these, it has been determined that modern extraction methods are more applicable to nature-friendly methods than traditional methods. Traditional extraction methods including maceration, pressing, infusion, digestion, percolation, decoction, reflux, tincture, distillation, and soxhlet methods and modern extraction methods including pressurized liquid extraction, supercritical fluid extraction, ultrasonic assisted extraction, microwave assisted extraction, pulsed electric field extraction, enzyme assisted extraction methods and their variation parameters were investigated. It has been seen that modern extraction methods are performed in less amount of sample, lower volume of solvent, lower energy consumption and shorter extraction times compared to traditional methods. Within the scope of the study, considering all these, it has been determined that modern extraction methods are more applicable nature-friendly methods than traditional methods.
Keywords: 7. Clean energy